منازعات المؤسسة العمومية الاقتصادية الآيلة للقضاء العادي في الجزائر بعد الإصلاحات الهيكلية لسنة 1988 - فرج,رشيد; أحمودة,يوسف (University of Eloued جامعة الوادي, 2024)
لقد أعتبرت المؤسسة العمومية الاقتصادية بعد الإصلاحات الهيكلية لسنة 1988 شخص من أشخاص القانون الخاص في النظام القانوني الجزائري بعد إكتسابها لصفة التجارية دون فقدها لصفة العمومية تماما، وهو الأمر الذي جعلها تخضع لقانون مزدوج وهجين وقضاء بذات الصفة غلبت عليه جهة القضاء العادي ومرد ذلك كون أغلب المعاملات التجارية تسير وفق منطق الربح والخسارة وتستبعد إمتيازات السلطة العامة غير أن الأمر ليس على إطلاقه كون الدولة الجزائرية لا تمنح إستقلالية حقيقية لهاته المؤسسة وفق ما يقتضيه النظام الاقتصادي العالمي الجديد وعلى أساس ذلك تقاسمت منازعات هذه الأخيرة جهات القضاء العادي والإداري ومرد ذلك للطبيعة القانونية الخاصة والمزدوجة لها. Abstract: After the structural reforms of 1988, the public economic institution was considered a private law person in the Algerian legal system after acquiring commercial status without losing its public status altogether. this made it subject to a double and hybrid law and a judiciary in the same capacity, which was dominated by the ordinary judiciary, because most commercial transactions proceed according to the logic of profit and loss and exclude the privileges of the public authority, but this is not the case because the Algerian state does not grant real independence to this institution as required by the system on the basis of this, the disputes of the latter were shared by the ordinary and administrative courts, due to their special and dual legal nature.
Keywords: القضاء العادي; القضاء الإداري; المؤسسة العمومية الاقتصادية; صفة التجارية; صفة العمومية; ordinary judiciary; administrative judiciary; public economic institution; commercial status; public status